What Is the Evidence for Harm of Neuromuscular Blockade and Corticosteroid Use in the Intensive Care Unit? - Annane, Djillali (Seminars in Respiratory and Critical Care Medicine, 2016)
Neuromuscular blocking agents and corticosteroids are widely used in medicine and in particular in the intensive care unit (ICU). Neuromuscular blockade is commonly used to ease tracheal intubation, to optimize mechanical ventilation and oxygenation in acute respiratory disorders such as status asthmaticus and acute respiratory distress syndrome (ARDS), to prevent shivering during therapeutic hypothermia, and also in patients with elevated intracranial pressure. In the ICU, patients with sepsis, ARDS, community-acquired pneumonia, exacerbation of chronic obstructive pulmonary disease, severe asthma, or trauma may receive corticosteroids. It is not rare that ICU patients receive concomitantly neuromuscular blocking drugs and corticosteroids. Among the various serious adverse reactions to these drugs, secondary infection and ICU-acquired weakness may place a burden to the health-care system by resulting in substantial cost and long-term morbidity. Both superinfections and ICU-acquired paresis are more likely when high doses of fluorinated corticosteroids are combined with prolonged treatment with a long-acting non-depolarizing neuromuscular blocker. Modern ICU practices favor lower dose of corticosteroids and very short course of short-acting curare for the management of sepsis or ARDS. Recent trials provided no evidence for increased risk of secondary infections or critical illness neuromyopathy in patients with sepsis or ARDS with the use of corticosteroids or neuromuscular blockers.
Keywords: neuromuscular blockade; critical illness neuromyopathy; corticosteroids; ICU